KUALITAS PELAYANAN KESEHATAN BAGI PASIEN PEMEGANG KARTU BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) DI RUMAH SAKIT MULIA HATI WONOGIRI - Donandro, Oryza (Transformasi, 2015)
This study aimed to describe the quality of health care for patients BPJS Program at theHospital Noble Heart Wonogiri. The method used is descriptive quantitative data collected byquestionnaire and documentation. The samples used in this study is 43 people. Data analysistechniques used using descriptive statistical analysis using frequency distribution table.Results of the data analysis we concluded the service quality Noble Heart Hospital onpatients Wonogiri BPJS cardholders using indicators of quality of service, is as follows:Indicators of reliability (reliability) based on research results is quite good. Indicatorresponsiveness (responsiveness) less employees to respond to patient complaints. Indicatorsassurance (guarantee) based on research results is quite good. Indicators empathy (attention)based on the research results have been good. Indicators of real evidence (tangibles) basedon the results of the study are adequate.Keywords: Reliability, responsiveness, assurance, empathy, and tangibles.